(untitled) (Studia theodisca, 2017)
Review of Friedrich Hölderlin’s book Iperione o l’eremita in Grecia (2015), by Francesco Rossi. Review of Friedrich Hölderlin’s book Epistolario. Lettere e dediche (2015), by Vivetta Vivarelli. Review of Dieter Burdorf’s book Friedrich Hölderlin (2012), by Michele Vangi. Review of Romano Guardini’s book Hölderlin (2014), by Daniele Goldoni. Review of Laura Anna Macor’s book Die Bestimmung des Menschen (1748-1800). Eine Begriffsgeschichte (2013), by Lorenzo Leonardo Pizzichemi. Review of Marco Menicacci’s book Mario Luzi e la poesia tedesca. Novalis, Hölderlin, Rilke (2014), by Sara Bubola.